Learning to Teach in the Secondary School : a Companion to School Experience. - Capel, Susan (Learning to teach subjects in the secondary school series., 2013)
Learning to teach involves hard work and careful preparation. To become an effective teacher requires subject knowledge, an understanding of your pupils and how they learn and the confidence to respond to dynamic classroom situations. Learning to Teach in the Secondary School 6th edition offers a comprehensive, in-depth and practical introduction to the skills needed to qualify as a teacher, and is designed to help you to develop those qualities that lead to good practice and a successful future in education. With a focus on evidence-based practice and writte.